Interactive effect of irrigation schedules and fertigation levels on fruit yield, quality and plant nutrition of Nagpur mandarin (Citrus reticulata) - SHIRGURE, P S; SRIVASTAVA, A K; HUCHCHE, A D; PATIL, PRAKASH (The Indian Journal of Agricultural Sciences, 2016)
Water and nutrient-useefficiency, both are considered as pre-requisites for sustained citrus productivity. The interactive effect of irrigation and fertigation levels on growth, yield and quality of 11-year-old Nagpur mandarin (Citrus reticulata Blanco) was studied through a field experiment during 2010-13 at ICAR-Central Citrus Research Institute (Formerly NRCC), Nagpur under AICRP Fruits. The experiment was laid out in split-plot design with nine treatment combinations, comprising three irrigation levels (70 %, 80 % and 90 % of daily evaporation replenishment) and three fertigation levels (60 %, 70 % and 80 % RDF based NPK doses) replicated six times. Canopy volume (74.9 m3) and fruit yield (19.2 tonnes/ha) were observed maximum with the drip irrigation scheduled at 80 % ER combined with 80 % RDF fertigation. The fruit quality parameters, such as fruit weight (129.2 g), juice percentage (45.05 %), TSS (10.27o Brix) and lowest acidity (0.81) were observed favorable with irrigation at 80% and fertigation at 80% RDF, in addition to maximum nutrient concentration in index leaves ( 2.38 % N, 0.12 % P and 1.50 % K) duly supported by changes in available pool of nutrients in soil (123.8 mg/kg N, 14.8 mg/kg P2O5 and 261.2 mg/kg K2O). Interestingly yield efficiency computed as fruit yield per unit canopy volume was also observed maximum (0.26) with treatment carrying irrigation at 80% ER and fertigation with 80% RDF. The sustained productivity of Nagpur mandarin can be achieved with irrigation scheduled at 80 % ER along with fertigation technology at 80 % RDF without any potential nutrient mining.